(untitled) (Bangladesh Armed Forces Medical Journal, 2024)
Background: Corneal Collagen Cross Linking (CXL) incorporated with riboflavin solution activated by UV (Ultraviolet) irradiation is a modern promising treatment protocol for keratoconus. Evaluation of the clinical effect of CXL treatment on keratoconus patients was the aim of this study. Methods: This Quasi Experimental (before-and-after) study was comprised with 50 patients, having progressive keratoconus (progression was documented by Corneal Topography), reported to Cornea Clinic, CMH Dhaka, from February 2022 to January 2023. Before and after the CXL procedure; un-corrected and best-corrected visual acuity of study population was documented using Snellen visual acuity chart. Auto-refractometry readings were also noted. Results: Among the 50 study subjects; 26 (52%) were men and 24 (48%) were female, age was 24.14 ± 5.07 (mean+SD) years and age range was 18-35 years. Mean preoperative spherical power was −1.84 ± 0.82 Diopter (D) and mean cylindrical power was −3.66 ± 0.97 D. Postoperatively, mean spherical power was found −1.15 ± 0.55 D and mean cylindrical power was −2.87 ± 0.99 D. After CXL treatment; significant vision improvement found in 15 (30%) patients (p<0.05). Conclusion: Despite strengthening the corneal stromal collagen bond and halting the keratoconus progression, CXL treatment stabilize the refractive status of keratoconus patient and also in some extent, it improves vision. Bangladesh Armed Forces Med J Vol 56 No (2) December 2023, pp 45-50